Investigation on metal diaphragm of pulse separation device in dual-pulse solid rocket motor. (March 2017) - Chunguang, Wang; Cong, Chen; Quanbin, Ren; Ke, Chen
The theories of circular plates with large deflection and fracture mechanics were employed to investigate the calculating formula of stress intensity factor on prefab gap. The relationship of the opening pressure with physical dimensions of hard pulse separation device (PSD) was analyzed to achieve the feasible configuration of metal diaphragm, which could play a very important role in dual-pulse solid rocket motor. Moreover, six specific single-term tests of the metal diaphragm were conducted to validate the computing precision of designing formula. In addition, three kinds of scale experiments, e.g. the bearing test, opening test, and associated test were performed to explore the working characters of hard pulse separation device. The results indicate that the error between the experimental results and designing results is 4.4%, and the method can be applied to design the physical dimensions of metal diaphragm. The performances of bearing ability, sealability, opening and melt of PSD have been demonstrated. The results show that this kind of PSD can satisfy the requirements of dual-pulse solid rocket motor very well.